Patterns and risk factors of avian influenza A(H5) and A(H9) virus infection in pigeons and quail at live bird markets in Bangladesh, 2017–2021 - Islam, Ariful; Islam, Shariful; Amin, Emama; Hasan, Rashedul; Hassan, Mohammad Mahmudul; Miah, Mojnu; Samad, Mohammed Abdus; Shirin, Tahmina; Hossain, Mohammad Enayet; Rahman, Mohammed Ziaur (Frontiers in Veterinary Science, 2022)
The Avian Influenza Virus (AIV) impacts poultry production, food security, livelihoods, and the risk of transmission to humans. Poultry farming, like pigeons and quail , is a growing sector in Bangladesh. However, the role of pigeon and quail in AIV transmission is not fully understood. Hence, we conducted this study to investigate the prevalence and risk factors of AIV subtypes in pigeons and quails at LBMs in Bangladesh. We collected oropharyngeal and cloacal swab samples from 626 birds in 8 districts of Bangladesh from 2017 to 2021. We tested the samples for the matrix gene (M gene) followed by H5, H7, and H9 subtypes using rRT-PCR. We used exploratory analysis to investigate the seasonal and temporal patterns of AIV and a mixed-effect logistic model to identify the variable that influences AIV. The overall prevalence of AIV was 25.56%, where 17.36% was in pigeons and 38.75% was in quail. The prevalence of A/H5, A/H9, and A/H5/H9 in quail is 4.17%, 17.92%, and 1.67%; while 2.85%, 2.59%, and 0.26% in pigeons, respectively. The AIV infection was higher in the dry season in both pigeons and quail. The model showed that the vendors having waterfowl (AOR: 2.13; 95% CI: 1.04-4.33), purchasing birds from the wholesale market (AOR: 2.96; 95% CI: 1.48-5.92) instead of farms, mixing sick birds with the healthy ones (AOR: 1.60; 95% CI: 1.04-2.45) and mingling unsold birds with new birds (AOR: 3.07; 95% CI: 2.01-4.70) were significantly more likely to be positive for AIV compared with vendors that did not have these characteristics. We also found that the odds of AIV were more than twice as high in quail (AOR: 2.57; 95% CI: 1.61-4.11) as in pigeons. Furthermore, the likelihood of AIV detection was 4.19 times higher in sick and dead birds (95% CI: 2.38–7.35) than in healthy birds. Our study revealed that proper hygienic practices at the vendors in LBM are not maintained. We recommend improving biosecurity practices at the vendor level in LBM to limit the risk of AIV infection in pigeons and quail in Bangladesh.